2013
DOI: 10.1158/1078-0432.ccr-13-1110
|View full text |Cite
|
Sign up to set email alerts
|

The Janus Kinases Inhibitor AZD1480 Attenuates Growth of Small Cell Lung Cancers In Vitro and In Vivo

Abstract: Purpose The prognosis of small cell lung cancer (SCLC) is poor, and there has been very little progress in the medical treatment of SCLC in the past two decades. We investigated the potential of janus kinases (JAKs) inhibitor AZD1480 for treatment of SCLC in vitro and in vivo. Experimental Design JAK1 or JAK2 were inhibited by AZD1480 or siRNAs, and the effect of inhibition of JAK gene family on SCLC cell viability was evaluated. The effect of AZD1480 on cell cycle distribution and apoptosis induction were s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
3
12
0
Order By: Relevance
“…In vitro and animal data indicates that targeting JAK2 with siRNA will inhibit the growth of SCLC. AZD1480 (which targets JAK1/2/3, FLT3 and Aurora kinase) has single agent activity as well as synergy with existing chemotherapy 91 .…”
Section: New Sclc Targets and Drugsmentioning
confidence: 99%
“…In vitro and animal data indicates that targeting JAK2 with siRNA will inhibit the growth of SCLC. AZD1480 (which targets JAK1/2/3, FLT3 and Aurora kinase) has single agent activity as well as synergy with existing chemotherapy 91 .…”
Section: New Sclc Targets and Drugsmentioning
confidence: 99%
“…For example, the JAK2 inhibitor AZD1480 blocks STAT3 activation in several solid tumor cell lines, including several small and nonsmall cell lung cancer cell lines, and suppresses the growth cancer xenografts harboring persistent STAT3 activation. [115][116][117] In NSCLC cells, IL-6 neutralizing antibody has been shown to inhibit tumor growth in a mouse xenograft model by suppressing JAK1/STAT3 signaling. 50 Moreover, the JAK1/2 inhibitor ruxolitinib significantly slowed down the growth of xenografted NSCLC cells in nude mice.…”
Section: Stat3 As a Therapeutic Target For Lung Cancer Treatmentmentioning
confidence: 99%
“…Of those 15 PPIs, six included JAK1 as a binding partner, two included JAK2, and one was the JAK1-JAK2 interaction. It has recently been shown that inhibition of JAKs attenuates growth of small cell lung cancers in vitro and in vivo [58], and that activation of JAK signaling induces resistance to EGFR mutations in non-small cell lung cancers [59]. Also of potential interest is an ATM-NBN interaction that is involved in double-strand DNA break repair and PI3KR1 interactions involved in activation of the PI3K pathway.…”
Section: Resultsmentioning
confidence: 99%